Two 2015 Summer Conferences. (2nd April 2016) - Polansky, Patricia
ABSTRACT: The author reports on two conferences she attended during the summer of 2015. The first was the annual conference of the British Slavic (Slavonic) librarians' organization, the Council for Slavonic and East European Library and Information Services (COSEELIS) in Cambridge, England. The second was the ninth World Congress of the International Council for Central and East European Studies (ICCEES), in the Makuhari convention center in Chiba city, outside of Tokyo.